2010
DOI: 10.1161/atvbaha.109.200824
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis and Vascular Dementia

Abstract: V ascular dementia (VaD) comprises a group of syndromes caused by vascular lesions in the brain. Cognitive impairment may follow a single cortical or lacunar infarct in a strategic area of the brain, multiple infarcts, small-vessel disease (leukoaraiosis), intracerebral hemorrhage, or any of these conditions coexisting with Alzheimer dementia (so-called mixed dementia). Depending on case mix and the type of observational study, 10% of patients already have dementia before their first stroke, 10% develop it soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…15 Levels of both vWF and FVIII are associated with thrombosis, 16 and were recently linked to dementia risk. 17 A recent report demonstrating an association between blood type AB and stroke risk found that 60% of that association was mediated by differences in FVIII level. 18 Although ABO blood group is a CVD risk factor, we are not aware of studies on its relationship with cognitive impairment.…”
mentioning
confidence: 99%
“…15 Levels of both vWF and FVIII are associated with thrombosis, 16 and were recently linked to dementia risk. 17 A recent report demonstrating an association between blood type AB and stroke risk found that 60% of that association was mediated by differences in FVIII level. 18 Although ABO blood group is a CVD risk factor, we are not aware of studies on its relationship with cognitive impairment.…”
mentioning
confidence: 99%
“…A dose-dependent relationship between FVIII levels and the occurrence of thrombotic events (including overt ischemic stroke) has also been observed [4][5][6][7][8]. Further studies have linked FVIII, a potential therapeutic target, with dementia risk [9,10] as well as risk for cognitive impairment in a study of men [11]. Previous research in the US-based Cardiovascular Health Study (CHS) found an association between higher FVIII and incident cardiovascular disease, stroke, and death in the older general study population [12], but these studies did not investigate covert WMH or cognitive decline.…”
Section: Introductionmentioning
confidence: 88%
“…Although sample size was an issue in all of these studies, the Dutch studies had slightly more robust data due to repeats. Nonetheless, further research is necessary to establish the roles of these inflammatory markers in cognitive decline ( 113 , 114 ).…”
Section: Coagulation and Complement Systems In Vascular Dementiamentioning
confidence: 99%